Impacts of inherent o-containing functional groups on the surface properties of shengli lignite - Wang, Y.; Zhou, J.; Bai, L.; Chen, Y.; Zhang, Shu; Lin, X. (American Chemical Society, 2014)
Shengli (SL) lignite was thermally treated by heating at 200-350 C in an effort to reduce the number of O-containing functional groups and water present. The presence of carboxyl groups, phenolic hydroxyl groups, and methoxy groups was characterized using a chemical titration method. The moisture holding capacity (MHC), wettability, and ? potential of the SL lignite were measured before and after the low-temperature heat treatment. The results revealed that the main reactions that occurred below 350 C were decarboxylation and dehydration, corresponding to the decomposition of more than 60% of the carboxyl groups and phenolic hydroxyl groups. SL lignite treated at 350 C displayed an approximately 50% reduction in its MHC. The O-containing functional groups (the carboxyl groups, in particular) played an important role in water adsorption, indicating that the formation of the hydrogen bond between the O-containing functional groups and water contributed most significantly to the water adsorption process. The contact angle decreased as the number of hydrophilic sites decreased as a result of the decomposition of O-containing functional groups. The ? potential of the SL lignite decreased significantly as the concentration of O-containing functional groups decreased. MHC was successfully correlated with the presence of O-containing functional groups and the quantity of surface area without oxygen groups, as follows: MHC = 2.655[-COOH] + 2.912[-OH] + 0.209[-OCH 3 ] - 3.321S non-O + 1.341, where S non-O for the lignite is defined as S non-O = S i (1 - C i /C 0 ), where S i is the surface area of the lignite and C i and C 0 are the total contents of O-containing functional groups in the heat-treatment or as-received lignites. © 2014 American Chemical Society.